Predictors for pharmacological therapy and perinatal outcomes with metformin treatment in women with gestational diabetes - Brzozowska, Malgorzata M.; Puvanendran, Anita; Bliuc, Dana; Zuschmann, Andrew; Piotrowicz, Agata K.; O’Sullivan, Anthony (Frontiers in Endocrinology, 2023)
Background: The prevalence of gestational diabetes mellitus (GDM) has been increasing in Australia and worldwide. The study aims were to examine, in comparison with dietary intervention, perinatal outcomes for women with gestational diabetes who were attending a single hospital clinic and to identify predictors for their pharmacological GDM treatment. Methods: A prospective, observational study of women with GDM, treated with “Diet, N= 50”, “Metformin, N = 35”, “Metformin and Insulin, N = 46” or “Insulin, N = 20”. Findings: The mean BMI for the whole cohort was 25.8 ± 4.7 kg/m2. The Metformin group, compared to the Diet group, had OR=3.1 (95% CI:1.13 to 8.25) for caesarean section birth (LSCS) compared to normal vaginal birth mode with no longer such a significant association after controlling for the number of their elective LSCS. The insulin treated group had the highest number of small for gestational age neonates (20%, p<0.05) with neonatal hypoglycaemia (25%, p< 0.05). Fasting glucose value on oral GTT (glucose tolerance test) was the strongest predictor for a pharmacological intervention requirement with OR = 2.77 (95CI%: 1.16 to 6.61), followed by timing of OGTT with OR=0.90 (95% CI: 0.83 to 0.97) and previous pregnancy loss with OR=0.28 (95% CI:0.10 to 0.74). Interpretation: These data suggest that metformin may be a safe alternative treatment to insulin treatment in GDM. Raised fasting glucose on oral GTT was the strongest indicator that GDM women with BMI < 35 kg/m2 may require pharmacological therapy. Further studies are needed to identify the most effective and safe management of gestational diabetes within the public hospital setting. Australian New Zealand Clinical Trial Registry ANZCTR Trial Id: ACTRN12620000397910.